Do family physicians perceive electronic cigarette use as a harm reduction strategy for smokers? A survey from Istanbul - AY, NADİYE PINAR; HIDIROĞLU, SEYHAN (My University, 2022)
Background: E-cigarettes (ECs) are gaining popularity in Turkey among smokers. With the rapid increase of EC consumption, it is important to ascertain how family physicians (FPs) perceive ECs as they play a key role in providing smoking cessation services. Aim: Our main objectives were to determine FPs\" level of awareness and harm reduction perceptions of ECs and to delineate the factors associated with their counseling practices. Methods: This was a cross-sectional study with descriptive and analytical components. Data were collected through questionnaires. Questions mainly focused on demographic characteristics, knowledge and own use of ECs, general attitudes towards ECs, and daily practices while performing counseling on tobacco use. In order to control confounding factors, logistic regression analysis was performed. Findings: Among a total of 271 FPs, 49.1% (n = 133) were males and the median age (IQR) was 41 years (32-46). Almost one-fifth of the FPs (n = 52) reported that they did not provide counseling services to their smoking patients. Only 26.6% (n = 72) of the FPs stated that they felt confident enough to advise patients on smoking cessation. Of the FPs, 6.6% have stated that they have recommended ECs to their patients for smoking cessation with the strategy of harm reduction. Factors associated with providers\" recommendation of ECs to their patients as a harm reduction strategy included \"believing that ECs help smokers to quit, ECs could be vaped in closed areas, and ECs were healthier than combustible tobacco products\". Conclusion: In our study, FPs stated lack of confidence to advice patients on smoking cessation. Furthermore, they recommended ECs to their smoking patients as a harm reduction strategy. FPs\" confidence should be increased with the trainings based on recent evidence on ECs.
Keywords: e-cigarettes; family physician; harm reduction; nicotine addiction; smoking cessation; SMOKING-CESSATION; TOBACCO; ATTITUDES; HEALTH; INTERVENTIONS; BEHAVIORS; KNOWLEDGE; AWARENESS; PRODUCTS; EFFICACY; e-cigarettes; family physician; harm reduction; nicotine addiction; smoking cessation